Effectiveness of Implementing CHSE (Cleanliness, Health, Safety, Environment) Protocols in Dunia Fantasi, Jakarta, Indonesia - Putra, Ranandyo Muliawan; Rachmatullah, Adam; Ratu Bilqis, Linda Desafitri; Tarigan, Emenina; Ramadhan, Yusuf (Institut Pariwisata Trisakti, 2024)
The implementation of the CHSE (Cleanliness, Health, Safety, and Environment) Protocol at Dunia Fantasi Jakarta is a mandatory procedure for the business of tourism destinations in the pandemic-post-pandemic era or the new normal tourism era. The implementation of CHSE is expected to be able to create a safe, healthy, and environmentally friendly environment for all tourists and to be useful in supporting the sustainability of the tourism industry in providing a positive experience for tourists visiting these destinations. The research objective is to analyze everything about effectiveness of implementing the CHSE protocol in Dunia Fantasi Jakarta. The method that used in this study is a quantitative descriptive method, with a total of 68 respondents. The sample was selected by convenience sampling, where the data collection was carried out using a survey. The research of this test used the validity, reliability, and Kruskal Wallis tests to determine the significance level of each actor. In general, it can be concluded that the implementation of CHSE in Dunia Fantasi is classified as good or is at a score of 6. This indicates that the management is serious about implementing the CHSE protocol in every tourism room and public facility space in Dunia Fantasi. Keywords: tourism, CHSE, effectiveness, new normal tourism